Peran Teman Sebaya dalam Menurunkan Perilaku Merokok Pada Remaja Perempuan di Kota Yogyakarta - Putri, Tyas Aisyah; Wijaya, Devy Riyanti Adi (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2024)
Background. Smoking behavior can threaten women's health in the future. According to Riskesdas 2018, there has been an increase in female smokers aged over 15 years from 2016 to 2018. In 2016, 2.5% in 2018, 4.8%. Smoking for women in urban areas is often considered a modern lifestyle. Aim. This study aims to explore the experience of smoking behavior among adolescent girls in the city of Yogyakarta, including factors that can influence adolescent girls to smoke. Method. Qualitative phenomenological research with in-depth interviews and observations. Subjects were taken by purposive sampling, totaling ten people, namely teenage female smokers aged 18-21 years and their peers as triangulation informants. Data analysis uses thematic analysis. Result. Most female teenagers engage in their first smoking behavior at age 15-19. Adolescent girls know the dangers of smoking for women's health but tend to ignore it. Teenage girls smoking among women is now a common thing to do. Adolescent girls receive information about the dangers of smoking for women only on cigarette packs, but the information is limited. Conclusion. The role of peers in smoking behavior in adolescent girls is as a provider of encouragement, motivation, example, and pressure on other friends in smoking behavior. There is a real need for an exceptional mentoring program for teenage female smokers who want to quit smoking and to increase health promotion efforts regarding the dangers of smoking for women's health in every activity involving the community.